The genetic decomposition of students about infinite series through the ethnomathematics of Bengkulu, Indonesia. (February 2020) - Widada, W; Efendi, S; Herawaty, D; Nugroho, K U Z; Putri, F R
Abstract: The cognitive theory views individuals as active information processors, so that individuals were able to represent each information according to the level of knowledge they have. Student representation can be seen as its genetic decomposition. Ethnomathematics was a vehicle for unlimited series learning. The purpose of this study was to describe the genetical decomposition of students about infinite series through the Bengkulu ethnomathematics. This was the initial research from a series of development research. This stage we interviewed in depth 10 high school students in Bengkulu, Indonesia. The research instrument was the researchers themselves who were guided by interview guides about understanding concepts and the principle of infinite series. Interviews were conducted during and after Bengkulu's ethnomathematics learning. Data were analyzed through fixed comparison techniques. The results of this study were found that students can coordinate two or more actions about convergence of sequences, but not for convergence of infinite series. Conversely, there were students who can describe a particular object about converging an infinite series but not coordinated with the processes that were built for converging sequences. Also, there were students who can coordinate the action-process related objects so that a schema of converging sequence was formed, but for infinite series only in the form of separate actions or processes. The conclusion of this study was the genetic decomposition of students in understanding the infinite series through ethnomathematics learning at the intermediate level (inter level). The student before ethnomathematics learning was at the lower level (intra and pre-intra levels).